Supplemental Nutrition Assistance Program: Examining the Evidence to Define Benefit Adequacy - Institute of Medicine; National Research Council (The National Academies Press, 2013)
For many Americans who live at or below the poverty threshold, access to healthy foods at a reasonable price is a challenge that often places a strain on already limited resources and may compel them to make food choices that are contrary to current nutritional guidance. To help alleviate this problem, the U.S. Department of Agriculture (USDA) administers a number of nutrition assistance programs designed to improve access to healthy foods for low-income individuals and households. The largest of these programs is the Supplemental Nutrition Assistance Program (SNAP), formerly called the Food Stamp Program, which today serves more than 46 million Americans with a program cost in excess of $75 billion annually. The goals of SNAP include raising the level of nutrition among low-income households and maintaining adequate levels of nutrition by increasing the food purchasing power of low-income families. In response to questions about whether there are different ways to define the adequacy of SNAP allotments consistent with the program goals of improving food security and access to a healthy diet, USDA's Food and Nutrition Service (FNS) asked the Institute of Medicine (IOM) to conduct a study to examine the feasibility of defining the adequacy of SNAP allotments, specifically: the feasibility of establishing an objective, evidence-based, science-driven definition of the adequacy of SNAP allotments consistent with the program goals of improving food security and access to a healthy diet, as well as other relevant dimensions of adequacy; and data and analyses needed to support an evidence-based assessment of the adequacy of SNAP allotments. Supplemental Nutrition Assistance Program: Examining the Evidence to Define Benefit Adequacy reviews the current evidence, including the peer-reviewed published literature and peer-reviewed government reports. Although not given equal weight with peer-reviewed publications, some non-peer-reviewed publications from nongovernmental organizations and stakeholder groups also were considered because they provided additional insight into the behavioral aspects of participation in nutrition assistance programs. In addition to its evidence review, the committee held a data gathering workshop that tapped a range of expertise relevant to its task.
Keywords: Food and Nutrition

Nutrition Education in the K-12 Curriculum: The Role of National Standards: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The childhood obesity epidemic and related health consequences are urgent public health problems. Approximately one-third of America's young people are overweight or obese. Health problems once seen overwhelmingly in adults, such as type 2 diabetes, cardiovascular disease, and hypertension, are increasingly appearing in youth. Though the health of Americans has improved in many broad areas for decades, increases in obesity could erode these and future improvements. The IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation recognized the importance of the school environment in addressing the epidemic and recommended making schools a focal point for obesity prevention. The development and implementation of K-12 nutrition benchmarks, guides, or standards (for a discussion of these terms, see the next section of this chapter) would constitute a critical step in achieving this recommendation. National nutrition education curriculum standards could have a variety of benefits, including the following: Improving the consistency and effectiveness of nutrition education in schools; Preparing and training teachers and other education staff to help them provide effective nutrition education; Assisting colleges and universities in the development of courses in nutrition as part of teacher certification and in updating methods courses on how to integrate nutrition education in subject-matter areas in the classroom and in materials; and Establishing a framework for future collaborative efforts and partnerships to improve nutrition education. Nutrition Education in the K-12 Curriculum: The Role of National Standards is a summary of the workshop's presentations and discussions prepared from the workshop transcript and slides. This summary presents recommendations made by individual speakers.
Keywords: Food and Nutrition

Guidelines on Weight Gain and Pregnancy - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Being healthy is a topic that is on everyone's mind these days. If you are pregnant or may become pregnant in the future, it's really important. In 2009, the Institute of Medicine and the National Research Council published updated guidelines on weight gain during pregnancy that enhances your ability to have a healthy pregnancy and baby. This book provides vital information for expectant mothers or those trying to conceive.
Keywords: Health and Medicine

Implementing Guidelines on Weight Gain and Pregnancy - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Being healthy is a topic that is on everyone's mind these days. If you are pregnant or may become pregnant in the future, it's really important. In 2009, the Institute of Medicine and the National Research Council published updated guidelines on weight gain during pregnancy that enhances your ability to have a healthy pregnancy and baby. This book provides vital information for expectant mothers or those trying to conceive. Health care providers can do a lot to help women learn about the follow the guidelines. This book features the key points from the guidelines.
Keywords: Health and Medicine

Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger: Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2013)
Section 141 of The Healthy, Hunger-Free Kids Act of 20101 provides funding for a research program on the causes and consequences of childhood hunger and food insecurity, and the characteristics of households with childhood hunger and food insecurity, with a particular focus on efforts to improve the knowledge base regarding contributing factors, geographic distribution, programmatic effectiveness, public health and medical costs, and consequences for child development, well-being, and educational attainment. The Economic Research Service and Food and Nutrition Service of the US Department of Agriculture conducted two outreach efforts to obtain input from the research community and other stakeholders to help focus on areas and methods with the greatest research potential. First, Food and Nutrition Service sought written comments to selected questions through publication of a Federal Register Notice. The second option was to convene a workshop under the auspices of the Committee on National Statistics of the National Research Council and the Food and Nutrition Board of the Institute of Medicine. Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger is the summary of that workshop, convened in Fall 2012 to examine research gaps and opportunities to advance understanding of the causes and consequences of child hunger in the United States. This report reviews the adequacy of current knowledge, identifies substantial research gaps, and considers data availability of economic, health, social, cultural, demographic, and other factors that contribute to childhood hunger or food insecurity. It also considers the geographic distribution of childhood hunger and food insecurity; the extent to which existing federal assistance programs reduce childhood hunger and food insecurity; childhood hunger and food insecurity persistence, and the extent to which it is due to gaps in program coverage; and the inability of potential participants to access programs, or the insufficiency of program benefits or services. Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger will be a resource to inform discussions about the public health and medical costs of childhood hunger and food insecurity through its focus on determinants of child food insecurity and hunger, individual, community, and policy responses to hunger, impacts of child food insecurity and hunger, and measurement and surveillance issues.
Keywords: Food and Nutrition; Behavioral and Social Sciences; Health and Medicine

Challenges and Opportunities for Change in Food Marketing to Children and Youth: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The childhood obesity epidemic is an urgent public health problem. The most recent data available show that nearly 19 percent of boys and about 15 percent of girls aged 2-19 are obese, and almost a third of U.S. children and adolescents are overweight or obese (Ogden et al., 2012). The obesity epidemic will continue to take a substantial toll on the health of Americans. In the midst of this epidemic, children are exposed to an enormous amount of commercial advertising and marketing for food. In 2009, children aged 2-11 saw an average of more than 10 television food ads per day (Powell et al., 2011). Children see and hear advertising and marketing messages for food through many other channels as well, including radio, movies, billboards, and print media. Most notably, many new digital media venues and vehicles for food marketing have emerged in recent years, including Internet-based advergames, couponing on cell phones, and marketing on social networks, and much of this advertising is invisible to parents. The marketing of high-calorie, low-nutrient foods and beverages is linked to overweight and obesity. A major 2006 report from the Institute of Medicine (IOM) documents evidence that television advertising influences the food and beverage preferences, requests, and short-term consumption of children aged 2-11 (IOM, 2006). Challenges and Opportunities for Change in Food Marketing to Children and Youth also documents a body of evidence showing an association of television advertising with the adiposity of children and adolescents aged 2-18. The report notes the prevailing pattern that food and beverage products marketed to children and youth are often high in calories, fat, sugar, and sodium; are of low nutritional value; and tend to be from food groups Americans are already overconsuming. Furthermore, marketing messages that promote nutrition, healthful foods, or physical activity are scarce (IOM, 2006). To review progress and explore opportunities for action on food and beverage marketing that targets children and youth, the IOM's Standing Committee on Childhood Obesity Prevention held a workshop in Washington, DC, on November 5, 2012, titled "New Challenges and Opportunities in Food Marketing to Children and Youth."
Keywords: Food and Nutrition

The Human Microbiome, Diet, and Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The Food Forum convened a public workshop on February 22-23, 2012, to explore current and emerging knowledge of the human microbiome, its role in human health, its interaction with the diet, and the translation of new research findings into tools and products that improve the nutritional quality of the food supply. The Human Microbiome, Diet, and Health: Workshop Summary summarizes the presentations and discussions that took place during the workshop. Over the two day workshop, several themes covered included: The microbiome is integral to human physiology, health, and disease. The microbiome is arguably the most intimate connection that humans have with their external environment, mostly through diet. Given the emerging nature of research on the microbiome, some important methodology issues might still have to be resolved with respect to undersampling and a lack of causal and mechanistic studies. Dietary interventions intended to have an impact on host biology via their impact on the microbiome are being developed, and the market for these products is seeing tremendous success. However, the current regulatory framework poses challenges to industry interest and investment.
Keywords: Food and Nutrition

Creating Equal Opportunities for a Healthy Weight: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Creating Equal Opportunities for a Healthy Weight is the summary of a workshop convened by the Institute of Medicine's Standing Committee on Childhood Obesity Prevention in June 2013 to examine income, race, and ethnicity, and how these factors intersect with childhood obesity and its prevention. Registered participants, along with viewers of a simultaneous webcast of the workshop, heard a series of presentations by researchers, policy makers, advocates, and other stakeholders focused on health disparities associated with income, race, ethnicity, and other characteristics and on how these factors intersect with obesity and its prevention. The workshop featured invited presentations and discussions concerning physical activity, healthy food access, food marketing and messaging, and the roles of employers, health care professionals, and schools. The IOM 2012 report Accelerating Progress in Obesity Prevention acknowledged that a variety of characteristics linked historically to social exclusion or discrimination, including race, ethnicity, religion, socioeconomic status, gender, age, mental health, disability, sexual orientation or gender identity, geographic location, and immigrant status, can thereby affect opportunities for physical activity, healthy eating, health care, work, and education. In many parts of the United States, certain racial and ethnic groups and low-income individuals and families live, learn, work, and play in places that lack health-promoting resources such as parks, recreational facilities, high-quality grocery stores, and walkable streets. These same neighborhoods may have characteristics such as heavy traffic or other unsafe conditions that discourage people from walking or being physically active outdoors. The combination of unhealthy social and environmental risk factors, including limited access to healthy foods and opportunities for physical activity, can contribute to increased levels of chronic stress among community members, which have been linked to increased levels of sedentary activity and increased calorie consumption. Creating Equal Opportunities for a Healthy Weight focuses on the key obesity prevention goals and recommendations outlined in Accelerating Progress in Obesity Prevention through the lens of health equity. This report explores critical aspects of obesity prevention, while discussing potential future research, policy, and action that could lead to equity in opportunities to achieve a healthy weight.
Keywords: Food and Nutrition

Sodium Intake in Populations: Assessment of Evidence - Institute of Medicine (The National Academies Press, 2013)
Despite efforts over the past several decades to reduce sodium intake in the United States, adults still consume an average of 3,400 mg of sodium every day. A number of scientific bodies and professional health organizations, including the American Heart Association, the American Medical Association, and the American Public Health Association, support reducing dietary sodium intake. These organizations support a common goal to reduce daily sodium intake to less than 2,300 milligrams and further reduce intake to 1,500 mg among persons who are 51 years of age and older and those of any age who are African-American or have hypertension, diabetes, or chronic kidney disease. A substantial body of evidence supports these efforts to reduce sodium intake. This evidence links excessive dietary sodium to high blood pressure, a surrogate marker for cardiovascular disease (CVD), stroke, and cardiac-related mortality. However, concerns have been raised that a low sodium intake may adversely affect certain risk factors, including blood lipids and insulin resistance, and thus potentially increase risk of heart disease and stroke. In fact, several recent reports have challenged sodium reduction in the population as a strategy to reduce this risk. Sodium Intake in Populations recognizes the limitations of the available evidence, and explains that there is no consistent evidence to support an association between sodium intake and either a beneficial or adverse effect on most direct health outcomes other than some CVD outcomes (including stroke and CVD mortality) and all-cause mortality. Some evidence suggested that decreasing sodium intake could possibly reduce the risk of gastric cancer. However, the evidence was too limited to conclude the converse—that higher sodium intake could possibly increase the risk of gastric cancer. Interpreting these findings was particularly challenging because most studies were conducted outside the United States in populations consuming much higher levels of sodium than those consumed in this country. Sodium Intake in Populations is a summary of the findings and conclusions on evidence for associations between sodium intake and risk of CVD-related events and mortality.
Keywords: Food and Nutrition

Leveraging Action to Support Dissemination of the Pregnancy Weight Gain Guidelines: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Since 1990, when the last guidelines for weight gain during pregnancy were issued, the average body weight of women entering their childbearing years has increased considerably, with a greater percentage of these women now classified as overweight or obese. Women of childbearing age are also more likely to have chronic conditions such as high blood pressure or diabetes and to be at risk for poor maternal and child health outcomes. All of these factors increase the likelihood of poor pregnancy outcomes for women and their infants. As part of the continuing effort of The Institute of Medicine (IOM) and the National Research Council (NRC) to promote the revised pregnancy weight gain guidelines recommended in their 2009 study Weight Gain During Pregnancy: Reexamining the Guidelines, the IOM and NRC convened a workshop in March, 2013, to engage interested stakeholders, organizations, and federal agencies in a discussion of issues related to encouraging behavior change that would reflect the updated guidelines on weight gain during pregnancy. During the workshop, the IOM and NRC presented newly developed information resources to support guidance based on the recommendations of the 2009 report. Leveraging Action to Support Dissemination of the Pregnancy Weight Gain Guidelines summarizes the workshop's keynote address and the various presentations and discussions from the workshop, highlighting issues raised by presenters and attendees. Interested stakeholders, organizations, health professionals, and federal agencies met to discuss issues related to encouraging behavior change that would reflect the updated guidelines on weight gain during pregnancy. This report discusses conceptual products as well as products developed for dissemination, ways to facilitate and support behavior change to achieve healthy weight pre- and postpregnancy, and how to put the weight gain guidelines into action to implement change.
Keywords: Health and Medicine; Food and Nutrition

IOM Pregnancy Weight Trackers Assembly: Five Common Myths Flier - Institute of Medicine (The National Academies Press, 2013)
Keywords: Health and Medicine; Food and Nutrition

IOM Pregnancy Weight Trackers Assembly: Weight Tracker Postcard - Institute of Medicine (The National Academies Press, 2013)
Keywords: Health and Medicine; Food and Nutrition

IOM Pregnancy Weight Trackers Assembly: Weight Tracker Mini Booklet - Institute of Medicine (The National Academies Press, 2013)
Keywords: Health and Medicine; Food and Nutrition

Evaluating Obesity Prevention Efforts: A Plan for Measuring Progress - Institute of Medicine (The National Academies Press, 2013)
Obesity poses one of the greatest public health challenges of the 21st century, creating serious health, economic, and social consequences for individuals and society. Despite acceleration in efforts to characterize, comprehend, and act on this problem, including implementation of preventive interventions, further understanding is needed on the progress and effectiveness of these interventions. Evaluating Obesity Prevention Efforts develops a concise and actionable plan for measuring the nation's progress in obesity prevention efforts—specifically, the success of policy and environmental strategies recommended in the 2012 IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation. This book offers a framework that will provide guidance for systematic and routine planning, implementation, and evaluation of the advancement of obesity prevention efforts. This framework is for specific use with the goals and strategies from the 2012 report and can be used to assess the progress made in every community and throughout the country, with the ultimate goal of reducing the obesity epidemic. It offers potentially valuable guidance in improving the quality and effect of the actions being implemented. The recommendations of Evaluating Obesity Prevention Efforts focus on efforts to increase the likelihood that actions taken to prevent obesity will be evaluated, that their progress in accelerating the prevention of obesity will be monitored, and that the most promising practices will be widely disseminated.
Keywords: Food and Nutrition; Health and Medicine

Educating the Student Body: Taking Physical Activity and Physical Education to School - Institute of Medicine (The National Academies Press, 2013)
Physical inactivity is a key determinant of health across the lifespan. A lack of activity increases the risk of heart disease, colon and breast cancer, diabetes mellitus, hypertension, osteoporosis, anxiety and depression and others diseases. Emerging literature has suggested that in terms of mortality, the global population health burden of physical inactivity approaches that of cigarette smoking. The prevalence and substantial disease risk associated with physical inactivity has been described as a pandemic. The prevalence, health impact, and evidence of changeability all have resulted in calls for action to increase physical activity across the lifespan. In response to the need to find ways to make physical activity a health priority for youth, the Institute of Medicine's Committee on Physical Activity and Physical Education in the School Environment was formed. Its purpose was to review the current status of physical activity and physical education in the school environment, including before, during, and after school, and examine the influences of physical activity and physical education on the short and long term physical, cognitive and brain, and psychosocial health and development of children and adolescents. Educating the Student Body makes recommendations about approaches for strengthening and improving programs and policies for physical activity and physical education in the school environment. This report lays out a set of guiding principles to guide its work on these tasks. These included: recognizing the benefits of instilling life-long physical activity habits in children; the value of using systems thinking in improving physical activity and physical education in the school environment; the recognition of current disparities in opportunities and the need to achieve equity in physical activity and physical education; the importance of considering all types of school environments; the need to take into consideration the diversity of students as recommendations are developed. This report will be of interest to local and national policymakers, school officials, teachers, and the education community, researchers, professional organizations, and parents interested in physical activity, physical education, and health for school-aged children and adolescents.
Keywords: Health and Medicine; Education

Strengthening Human Resources Through Development of Candidate Core Competencies for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
One of the largest treatment gaps for mental, neurological, and substance use (MNS) disorders in the world can be seen in Sub-Saharan Africa (SSA). According to the World Health Organization (WHO), about 80% of people with serious MNS disorders living in low- and middle-income countries do not receive needed health services. A critical barrier to bridge this treatment gap is the ability to provide adequate human resources for the delivery of essential interventions for MNS disorders. An international workshop was convened in 2009, by the .S. Institute of Medicine (IOM) Forum on Neuroscience and Nervous Systems Disorders and the Uganda National Academy of Sciences (UNAS) Forum on Health and Nutrition, to bring together stakeholders from across SSA and to foster discussions about improving care for people suffering from MNS disorders and what steps, with potential for the greatest impact, might be considered to bridge the treatment gap. Due to the broad interest to further examine the treatment gap, the IOM forum organized a second workshop in Kampala, Uganda on September 4 and 5, 2012. The workshop's purpose was to discuss candidate core competencies that providers might need to help ensure the effective delivery of services for MNS disorders. The workshop focused specifically on depression, psychosis, epilepsy, and alcohol use disorders. Strengthening Human Resources Through Development of Candidate Core Competencies for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Workshop Summary outlines the presentations and discussions by expert panelists and participants of the plenary sessions of the workshop. This summary includes an overview of challenges faced by MNS providers in the SSA, perspectives on the next steps, the 2009 workshop, and more.
Keywords: Health and Medicine

Workforce Needs in Veterinary Medicine - National Research Council (The National Academies Press, 2013)
The U.S. veterinary medical profession contributes to society in diverse ways, from developing drugs and protecting the food supply to treating companion animals and investigating animal diseases in the wild. In a study of the issues related to the veterinary medical workforce, including demographics, workforce supply, trends affecting job availability, and capacity of the educational system to fill future demands, a National Research Council committee found that the profession faces important challenges in maintaining the economic sustainability of veterinary practice and education, building its scholarly foundations, and evolving veterinary service to meet changing societal needs. Many concerns about the profession came into focus following the outbreak of West Nile fever in 1999, and the subsequent outbreaks of SARS, monkeypox, bovine spongiform encephalopathy, highly pathogenic avian influenza, H1N1 influenza, and a variety of food safety and environmental issues heightened public concerns. They also raised further questions about the directions of veterinary medicine and the capacity of public health service the profession provides both in the United States and abroad. To address some of the problems facing the veterinary profession, greater public and private support for education and research in veterinary medicine is needed. The public, policymakers, and even medical professionals are frequently unaware of how veterinary medicine fundamentally supports both animal and human health and well-being. This report seeks to broaden the public's understanding and attempts to anticipate some of the needs and measures that are essential for the profession to fulfill given its changing roles in the 21st century.
Keywords: Agriculture; Biology and Life Sciences

Using Science to Improve the BLM Wild Horse and Burro Program: A Way Forward - National Research Council (The National Academies Press, 2013)
Using Science to Improve the BLM Wild Horse and Burro Program: A Way Forward reviews the science that underpins the Bureau of Land Management's oversight of free-ranging horses and burros on federal public lands in the western United States, concluding that constructive changes could be implemented. The Wild Horse and Burro Program has not used scientifically rigorous methods to estimate the population sizes of horses and burros, to model the effects of management actions on the animals, or to assess the availability and use of forage on rangelands. Evidence suggests that horse populations are growing by 15 to 20 percent each year, a level that is unsustainable for maintaining healthy horse populations as well as healthy ecosystems. Promising fertility-control methods are available to help limit this population growth, however. In addition, science-based methods exist for improving population estimates, predicting the effects of management practices in order to maintain genetically diverse, healthy populations, and estimating the productivity of rangelands. Greater transparency in how science-based methods are used to inform management decisions may help increase public confidence in the Wild Horse and Burro Program.
Keywords: Agriculture

Toward Quality Measures for Population Health and the Leading Health Indicators - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Committee on Quality Measures for the Healthy People Leading Health Indicators was charged by the Office of the Assistant Secretary for Health to identify measures of quality for the 12 Leading Health Indicator (LHI) topics and 26 Leading Health Indicators in Healthy People 2020 (HP2020), the current version of the Department of Health and Human Services (HHS) 10-year agenda for improving the nation's health. The scope of work for this project is to use the nine aims for improvement of quality in public health (population-centered, equitable, proactive, health promoting, risk reducing, vigilant, transparent, effective, and efficient) as a framework to identify quality measures for the Healthy People Leading Health Indicators (LHIs). The committee reviewed existing literature on the 12 LHI topics and the 26 Leading Health Indicators. Quality measures for the LHIs that are aligned with the nine aims for improvement of quality in public health will be identified. When appropriate, alignments with the six Priority Areas for Improvement of Quality in Public Health will be noted in the Committee's report. Toward Quality Measures for Population Health and the Leading Health Indicators also address data reporting and analytical capacities that must be available to capture the measures and for demonstrating the value of the measures to improving population health. Toward Quality Measures for Population Health and the Leading Health Indicators provides recommendations for how the measures can be used across sectors of the public health and health care systems. The six priority areas (also known as drivers) are population health metrics and information technology; evidence-based practices, research, and evaluation; systems thinking; sustainability and stewardship; policy; and workforce and education.
Keywords: Health and Medicine

Oral Health Literacy: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Roundtable on Health Literacy focuses on bringing together leaders from the federal government, foundations, health plans, associations, and private companies to address challenges facing health literacy practice and research and to identify approaches to promote health literacy in both the public and private sectors. The roundtable serves to educate the public, press, and policy makers regarding the issues of health literacy, sponsoring workshops to discuss approaches to resolve health literacy challenges. It also builds partnerships to move the field of health literacy forward by translating research findings into practical strategies for implementation. The Roundtable held a workshop March 29, 2012, to explore the field of oral health literacy. The workshop was organized by an independent planning committee in accordance with the procedures of the National Academy of Sciences. The planning group was composed of Sharon Barrett, Benard P. Dreyer, Alice M. Horowitz, Clarence Pearson, and Rima Rudd. The role of the workshop planning committee was limited to planning the workshop. Unlike a consensus committee report, a workshop summary may not contain conclusions and recommendations, except as expressed by and attributed to individual presenters and participants. Therefore, the summary has been prepared by the workshop rapporteur as a factual summary of what occurred at the workshop.
Keywords: Health and Medicine

Report of the Treasurer for the Year Ended December 31, 2012 - National Academy of Sciences (The National Academies Press, 2013)
The income that supports the activities of the National Academy of Sciences (NAS) comes from two major sources: program revenue received from sponsors to pay for the myriad studies and other activities undertaken each year by the National Research Council (NRC), and a much smaller sum that is obtained from our endowment under the endowment spending policies adopted by the Council. The goal of the endowment is to provide stable support for the Academy's programs and activities. To achieve this goal, the Council, acting on the recommendations of the Finance Committee, has historically authorized spending from the portfolio at a rate designed to maintain the purchasing power of the endowment over time. This Report of the Treasure of the National Academy of Sciences presents the financial position and results of operations as well as a review of the endowment, trust, and other long-term investments portfolio activities of our Academy for the year ended December 31, 2012. While this book provides essential financial summary to key personnel, it also serves as a vital informative resource for various members of the public, private, and governmental sectors
Keywords: Policy for Science and Technology

Leveraging Culture to Address Health Inequalities: Examples from Native Communities: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Leveraging Culture to Address Health Inequalities: Examples from Native Communities is the summary of a workshop convened in November 2012 by the Roundtable on the Promotion of Health Equity and the Elimination of Health Disparities of the Institute of Medicine. The workshop brought together more than 100 health care providers, policy makers, program administrators, researchers, and Native advocates to discuss the sizable health inequities affecting Native American, Alaska Native, First Nation, and Pacific Islander populations and the potential role of culture in helping to reduce those inequities. This report summarizes the presentations and discussion of the workshop and includes case studies that examine programs aimed at diabetes prevention and management and cancer prevention and treatment programs. In Native American tradition, the medicine wheel encompasses four different components of health: physical, emotional, mental, and spiritual. Health and well-being require balance within and among all four components. Thus, whether someone remains healthy depends as much on what happens around that person as on what happens within. Leveraging Culture to Address Health Inequalities addresses the broad role of culture in contributing to and ameliorating health inequities.
Keywords: Health and Medicine

Design of the National Children's Study: A Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2013)
The Children's Health Act mandated the National Children's Study (NCS) in 2000 with one of its purposes being to authorize the National Institute of Child Health and Human Development (NICHD) to study the environmental influences (including physical, chemical, biological, and psychosocial) on children's health and development. The NCS examines all aspects of the environment including air, water, diet, noise, family dynamics, and genetics, on the growth, development, and health of children across the United States, for a period of 21 years. The purpose of NCS is to improve the health and well-being of children and to contribute to understanding the role of these factors on health and disease. The research plan for the NCS was developed from 2005 to 2007 in collaboration among the Interagency Coordinating Committee, the NCS Advisory Committee, the NCS Program Office, Westat, the Vanguard Center principal investigators, and federal scientists. The current design of the study, however, uses a separate pilot to assess quality of scientific output, logistics, and operations and a "Main Study" to examine exposure-outcome relationships. The NCS proposed the use of a multilayered cohort approach for the Main Study, which was one of the topics for discussion at the workshop that is the subject of this publication. In the fall of 2012, NICHD requested that the Committee on National Statistics (CNSTAT) of the NRC and the IOM convene a joint workshop, to be led by CNSTAT. The workshop was to focus on issues related to the overall design (including the framework for implementation) of the NCS. The committee was provided a background paper which it used to select the challenges that were discussed at the workshop. Design of the National Children's Study: A Workshop Summary presents an overview of the workshop held on January 11, 2013. The publication includes summaries of the four sessions of the workshop, a list of participants, and the agenda.
Keywords: Behavioral and Social Sciences; Health and Medicine

Making the Soldier Decisive on Future Battlefields - National Research Council (The National Academies Press, 2013)
The U.S. military does not believe its soldiers, sailors, airmen, and marines should be engaged in combat with adversaries on a "level playing field." Our combat individuals enter engagements to win. To that end, the United States has used its technical prowess and industrial capability to develop decisive weapons that overmatch those of potential enemies. In its current engagement—what has been identified as an "era of persistent conflict"— the nation's most important weapon is the dismounted soldier operating in small units. Today's soldier must be prepared to contend with both regular and irregular adversaries. Results in Iraq and Afghanistan show that, while the U.S. soldier is a formidable fighter, the contemporary suite of equipment and support does not afford the same high degree of overmatch capability exhibited by large weapons platforms—yet it is the soldier who ultimately will play the decisive role in restoring stability. Making the Soldier Decisive on Future Battlefields establishes the technical requirements for overmatch capability for dismounted soldiers operating individually or in small units. It prescribes technological and organizational capabilities needed to make the dismounted soldier a decisive weapon in a changing, uncertain, and complex future environment and provides the Army with 15 recommendations on how to focus its efforts to enable the soldier and tactical small unit (TSU) to achieve overmatch.
Keywords: Conflict and Security Issues; Engineering and Technology

Collecting Sexual Orientation and Gender Identity Data in Electronic Health Records: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Collecting Sexual Orientation and Gender Identity Data in Electronic Health Records: Workshop Summary reviews the statement of task set to the committee which required them to collect sexual orientation and gender identity data in electronic health records. This report summarizes the invited presentations and facilitated discussions about current practices around sexual orientation and gender identity data collection, the challenges in collecting these data, and ways in which these challenges can be overcome. Areas of focus for the workshop include the clinical rationale behind collecting these data, standardized questions that can be used to collect these data, mechanisms for supporting providers and patients in the collection of these data, technical specifications involved in creating standards for sexual orientation and gender identity data collection and exchange, and policy considerations related to the health information technology (HIT) Meaningful Use process being overseen by the Department of Health and Human Services. This report summarizes the workshop agenda, select invited speakers and discussants, and moderate the discussions. Invited participants will include lesbian, gay, bisexual, and transgender (LGBT) health care consumer advocates, providers with experience working with LGBT populations, HIT vendors and other HIT specialists, health care administrators, and policy makers.
Keywords: Health and Medicine; Computers and Information Technology

Developing and Strengthening the Global Supply Chain for Second-Line Drugs for Multidrug-Resistant Tuberculosis: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
To effectively treat patients diagnosed with drug-resistant (DR) tuberculosis (TB) and protect the population from further transmission of this infectious disease, an uninterrupted supply of quality-assured (QA), second-line anti-TB drugs (SLDs) is necessary. Patients diagnosed with multidrug-resistant tuberculosis (MDR TB)—a disease caused by strains of Mycobacterium tuberculosis (M.tb.) resistant to two primary TB drugs (isoniazid and rifampicin)—face lengthy treatment regimens of 2 years or more with daily, directly observed treatment (DOT) with SLDs that are less potent, more toxic, and more expensive than those used to treat drug-susceptible TB. From 2000 to 2009, only 0.2-0.5 percent of the estimated 5 million MDR TB cases globally were treated with drugs of known quality and in programs capable of delivering appropriate care (Keshavjee, 2012). The vast majority of MDR TB patients either died from lack of treatment or contributed to the spread of MDR TB in their communities. A strengthened global supply chain for SLDs could save lives by consistently delivering high quality medicines to more of the people who need them. This public workshop explored innovative solutions to the problem of how to get the right SLDs for MDR TB to people who critically need them. More specifically, the workshop examined current problems and potential opportunities for coordinated international efforts to ensure that a reliable and affordable supply of high-quality SLDs is available. Developing and Strengthening the Global Supply Chain for Second-Line Drugs for Multidrug-Resistant Tuberculosis: Workshop Summary covers the objectives of the workshop, which were to review: -To what extent and in what ways current mechanisms are or are not effectively accomplishing what is needed, including consideration of bottlenecks. -The advantages and disadvantages of centralization in the management of the global drug supply chain, and potential decentralized approaches to improve operations of the supply chain. -What can be learned from case studies and examples from other diseases (e.g., the Affordable Medicines Facility-malaria (AMFm) and the U.S. President's Emergency Plan for AIDS Relief [PEPFAR]) - The current allocation of responsibilities and roles of the private (including industry and nonprofit public health organizations) and public sectors, and examination of opportunities for enhancing and optimizing collaboration -Identification of potential innovative solutions to the problem
Keywords: Health and Medicine

U.S. Health in International Perspective: Shorter Lives, Poorer Health - Institute of Medicine; National Research Council (The National Academies Press, 2013)
The United States is among the wealthiest nations in the world, but it is far from the healthiest. Although life expectancy and survival rates in the United States have improved dramatically over the past century, Americans live shorter lives and experience more injuries and illnesses than people in other high-income countries. The U.S. health disadvantage cannot be attributed solely to the adverse health status of racial or ethnic minorities or poor people: even highly advantaged Americans are in worse health than their counterparts in other, "peer" countries. In light of the new and growing evidence about the U.S. health disadvantage, the National Institutes of Health asked the National Research Council (NRC) and the Institute of Medicine (IOM) to convene a panel of experts to study the issue. The Panel on Understanding Cross-National Health Differences Among High-Income Countries examined whether the U.S. health disadvantage exists across the life span, considered potential explanations, and assessed the larger implications of the findings. U.S. Health in International Perspective presents detailed evidence on the issue, explores the possible explanations for the shorter and less healthy lives of Americans than those of people in comparable countries, and recommends actions by both government and nongovernment agencies and organizations to address the U.S. health disadvantage.
Keywords: Behavioral and Social Sciences; Health and Medicine; Surveys and Statistics

Interprofessional Education for Collaboration: Learning How to Improve Health from Interprofessional Models Across the Continuum of Education to Practice: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Every year, the Global Forum undertakes two workshops whose topics are selected by the more than 55 members of the Forum. It was decided in this first year of the Forum's existence that the workshops should lay the foundation for future work of the Forum and the topic that could best provide this base of understanding was "interprofessional education." The first workshop took place August 29-30, 2012, and the second was on November 29-30, 2012. Both workshops focused on linkages between interprofessional education (IPE) and collaborative practice. The difference between them was that Workshop 1 set the stage for defining and understanding IPE while Workshop 2 brought in speakers from around the world to provide living histories of their experience working in and between interprofessional education and interprofessional or collaborative practice. A committee of health professional education experts planned, organized, and conducted a 2-day, interactive public workshop exploring issues related to innovations in health professions education (HPE). The committee involved educators and other innovators of curriculum development and pedagogy and will be drawn from at least four health disciplines. The workshop followed a high-level framework and established an orientation for the future work of the Global Forum on Innovations in Health Professional Education. Interprofessional Education for Collaboration: Learning How to Improve Health from Interprofessional Models Across the Continuum of Education to Practice summarizes the presentations and small group discussions that focused on innovations in five areas of HPE: 1. Curricular innovations - Concentrates on what is being taught to health professions' learners to meet evolving domestic and international needs; 2. Pedagogic innovations - Looks at how the information can be better taught to students and WHERE education can takes place; 3. Cultural elements - Addresses who is being taught by whom as a means of enhancing the effectiveness of the design, development and implementation of interprofessional HPE; 4. Human resources for health - Focuses on how capacity can be innovatively expanded to better ensure an adequate supply and mix of educated health workers based on local needs; and 5. Metrics - Addresses how one measures whether learner assessment and evaluation of educational impact and care delivery systems influence individual and population health.
Keywords: Health and Medicine; Education

Improving the Health, Safety, and Well-Being of Young Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Young adults are at a significant and pivotal time of life. They may seek higher education, launch their work lives, develop personal relationships and healthy habits, and pursue other endeavors that help set them on healthy and productive pathways. However, the transition to adulthood also can be a time of increased vulnerability and risk. Young adults may be unemployed and homeless, lack access to health care, suffer from mental health issues or other chronic health conditions, or engage in binge drinking, illicit drug use, or driving under the influence. Young adults are moving out of the services and systems that supported them as children and adolescents, but adult services and systems—for example, the adult health care system, the labor market, and the justice system—may not be well suited to supporting their needs. Improving the Health, Safety, and Well-Being of Young Adults is the summary of a workshop hosted by the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) in May, 2013. More than 250 researchers, practitioners, policy makers, and young adults presented and discussed research on the development, health, safety, and well-being of young adults. This report focuses on the developmental characteristics and attributes of this age group and its placement in the life course; how well young adults function across relevant sectors, including, for example, health and mental health, education, labor, justice, military, and foster care; and how the various sectors that intersect with young adults influence their health and well-being. Improving the Health, Safety, and Well-Being of Young Adults provides an overview of existing research and identifies research gaps and issues that deserve more intensive study. It also is meant to start a conversation aimed at a larger IOM/NRC effort to guide research, practices, and policies affecting young adults.
Keywords: Health and Medicine

Public Health Linkages with Sustainability: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
In 1992 world leaders met at the Earth Summit in Rio de Janeiro to reaffirm the Declaration of the United Nations Conference on the Human Environment that was established on June 16, 1972 in Stockholm. The meeting resulted in the adoption of Agenda 21 by the member states which is a framework for the transition to a more sustainable world. In 2012 the members gathered to assess and reaffirm the importance of progress towards the efforts of Agenda 21. In response to this the Institute of Medicine's (IOM's) Roundtable on Environmental Health Sciences, Research, and Medicine held a workshop to inform the policies that are discussed at the 2012 Earth Summit. The workshop, held in Woods Hole, Massachusetts on July 25-26, 2011, focused on the issue of sustainability and health as well as the linkages that are currently present between the two. The workshop included presentations and discussions which are summarized in Public Health Linkages with Sustainability: Workshop Summary. The report presents how different areas of public health, such as food and water resources, link to sustainability and opportunities or venues that can be examined.
Keywords: Health and Medicine

Evaluation of PEPFAR - Institute of Medicine (The National Academies Press, 2013)
The U.S. government supports programs to combat global HIV/AIDS through an initiative that is known as the President's Emergency Plan for AIDS Relief (PEPFAR). This initiative was originally authorized in the U.S. Leadership Against HIV/AIDS, Tuberculosis, and Malaria Act of 2003 and focused on an emergency response to the HIV/AIDS pandemic to deliver lifesaving care and treatment in low- and middle-income countries (LMICs) with the highest burdens of disease. It was subsequently reauthorized in the Tom Lantos and Henry J. Hyde U.S. Global Leadership Against HIV/AIDS, Tuberculosis, and Malaria Reauthorization Act of 2008 (the Lantos-Hyde Act). Evaluation of PEPFAR makes recommendations for improving the U.S. government's bilateral programs as part of the U.S. response to global HIV/AIDS. The overall aim of this evaluation is a forward-looking approach to track and anticipate the evolution of the U.S. response to global HIV to be positioned to inform the ability of the U.S. government to address key issues under consideration at the time of the report release.
Keywords: Health and Medicine

Health Literacy: Improving Health, Health Systems, and Health Policy Around the World: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The roots of health literacy can be traced back to the national literacy movement in India under Gandhi and to aid groups working in Africa to promote education and health. The term health literacy was first used in 1974 and described as "health education meeting minimal standards for all school grade levels". From that first use the definition of health literacy evolved during the next 30 years with official definitions promulgated by government agencies and large programs. Despite differences among these definitions, they all hold in common the idea that health literacy involves the need for people to understand information that helps them maintain good health. Although the United States produces a majority of the research on health literacy, Europe has strong multinational programs as well as research efforts, and health literacy experts in developing countries have created successful programs implemented on a community level. Given these distinct strengths of efforts worldwide, there are many opportunities for collaboration. International collaboration can harness the United States' research power, Europe's multilingual and multinational experience, and developing nations' community-based programs to create robust programs and research that reach people—not based on language or nationality but on need and value. A workshop on international health literacy efforts that feature presentations and discussion about health literacy interventions from various countries as well as other topics related to international health literacy was held as the basis for this report. Health Literacy: Improving Health, Health Systems, and Health Policy Around the World summarizes the findings and discussions at the workshop.
Keywords: Health and Medicine

Potential Health Risks to DOD Firing-Range Personnel from Recurrent Lead Exposure - National Research Council (The National Academies Press, 2013)
Lead is a ubiquitous metal in the environment, and its adverse effects on human health are well documented. Lead interacts at multiple cellular sites and can alter protein function in part through binding to amino acid sulfhydryl and carboxyl groups on a wide variety of structural and functional proteins. In addition, lead mimics calcium and other divalent cations, and it induces the increased production of cytotoxic reactive oxygen species. Adverse effects associated with lead exposure can be observed in multiple body systems, including the nervous, cardiovascular, renal, hematologic, immunologic, and reproductive systems. Lead exposure is also known to induce adverse developmental effects in utero and in the developing neonate. Lead poses an occupational health hazard, and the Occupational Safety and Health Administration (OSHA) developed a lead standard for general industry that regulates many workplace exposures to this metal. The standard was promulgated in 1978 and encompasses several approaches for reducing exposure to lead, including the establishment of a permissible exposure limit (PEL) of 50 μg/m3 in air (an 8-hour time-weighted average [TWA]), exposure guidelines for instituting medical surveillance, guidelines for removal from and return to work, and other risk-management strategies. An action level of 30 μg/m3 (an 8-hour TWA) for lead was established to trigger medical surveillance in employees exposed above that level for more than 30 days per year. Another provision is that any employee who has a blood lead level (BLL) of 60 μg/dL or higher or three consecutive BLLs averaging 50 μg/dL or higher must be removed from work involving lead exposure. An employee may resume work associated with lead exposure only after two BLLs are lower than 40 μg/dL. Thus, maintaining BLLs lower than 40 μg/dL was judged by OSHA to protect workers from adverse health effects. The OSHA standard also includes a recommendation that BLLs of workers who are planning a pregnancy be under 30μg/dL. In light of knowledge about the hazards posed by occupational lead exposure, the Department of Defense (DOD) asked the National Research Council to evaluate potential health risks from recurrent lead exposure of firing-range personnel. Specifically, DOD asked the National Research Council to determine whether current exposure standards for lead on DOD firing ranges protect its workers adequately.The committee also considered measures of cumulative lead dose. Potential Health Risks to DOD Firing-Range Personnel from Recurrent Lead Exposure will help to inform decisions about setting new air exposure limits for lead on firing ranges, about whether to implement limits for surface contamination, and about how to design lead-surveillance programs for range personnel appropriately.
Keywords: Health and Medicine; Conflict and Security Issues

Benefits, Burdens, and Prospects of the American Community Survey: Summary of a Workshop - National Research Council (The National Academies Press, 2013)
In June 2012, the Committee on National Statistics (sponsored by the U.S. Census Bureau) convened a Workshop on the Benefits (and Burdens) of the American Community Survey (ACS)—the detailed demographic and economic survey that began full-scale data collection in 2005 and that replaced the traditional "long form" in the 2010 census. ACS data are used by numerous federal agencies to administer programs, yet the ACS only moved from abstraction to reality for most users in 2010, when the first ACS estimates for small areas (based on 5 years of collected data) were made available. Hence, the workshop marked the opportunity to develop a picture of the breadth of the nonfederal user base of the ACS—among them, the media, policy research and evaluation groups (that distill ACS results for the media and broader public), state and local agencies, businesses and economic development organizations, and local and regional planning authorities—and to gather information on users' experiences with the first full releases of ACS products. In addition to covering innovative uses of the information now available on a continuous basis in the ACS, the workshop gave expression to the challenges and burdens associated with the survey: the time burden places on respondents, the challenges of explaining and interpreting estimates with increased levels of variability, and the privacy and confidentiality implications of some of the ACS content. Benefits, Burdens, and Prospects of the American Community Survey: Summary of a Workshop provides a factual summary of the workshop proceedings and hints at the contours of the ACS user constituency, providing important input to the ongoing review and refinement of the ACS program.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Reducing Maternal and Neonatal Mortality in Indonesia: Saving Lives, Saving the Future - National Research Council (The National Academies Press, 2013)
The Republic of Indonesia, home to over 240 million people, is the world's fourth most populous nation. Ethnically, culturally, and economically diverse, the Indonesian people are broadly dispersed across an archipelago of more than 13,000 islands. Rapid urbanization has given rise to one megacity (Jakarta) and to 10 other major metropolitan areas. And yet about half of Indonesians make their homes in rural areas of the country. Indonesia, a signatory to the United Nations Millennium Declaration, has committed to achieving the Millennium Development Goals (MDGs). However, recent estimates suggest that Indonesia will not achieve by the target date of 2015 MDG 4 - reduction by two-thirds of the 1990 under - 5 infant mortality rate (number of children under age 5 who die per 1,000 live births) - and MDG 5 - reduction by three-quarters of the 1990 maternal mortality ratio (number of maternal deaths within 28 days of childbirth in a given year per 100,000 live births). Although much has been achieved, complex and indeed difficult challenges will have to be overcome before maternal and infant mortality are brought into the MDG-prescribed range. Reducing Maternal and Neonatal Mortality in Indonesia is a joint study by the U.S. National Academy of Sciences and the Indonesian Academy of Sciences that evaluates the quality and consistency of the existing data on maternal and neonatal mortality; devises a strategy to achieve the Millennium Development Goals related to maternal mortality, fetal mortality (stillbirths), and neonatal mortality; and identifies the highest priority interventions and proposes steps toward development of an effective implementation plan. According to the UN Human Development Index (HDI), in 2012 Indonesia ranked 121st out of 185 countries in human development. However, over the last 20 years the rate of improvement in Indonesia's HDI ranking has exceeded the world average. This progress may be attributable in part to the fact that Indonesia has put considerable effort into meeting the MDGs. This report is intended to be a contribution toward achieving the Millennium Development Goals.
Keywords: Health and Medicine

Methods for Forecasting Demand and Quantifying Need for Rural Passenger Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Transit Cooperative Research Program (TCRP) Web-Only Document 58: Methods for Forecasting Demand and Quantifying Need for Rural Passenger Transportation supplements TCRP Report 161 by describing how the research team developed the report’s need and demand estimation methods, the findings of the analyses, and recommendations for functions to be used in estimation of need and demand.TCRP Report 161: Methods for Forecasting Demand and Quantifying Need for Rural Passenger Transportation: Final Workbook presents step-by-step procedures for quantifying the need for passenger transportation services and the demand that is likely to be generated if passenger transportation services are provided.
Keywords: Transportation and Infrastructure

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.
Keywords: Health and Medicine

International Regulatory Harmonization Amid Globalization of Drug Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The past several decades have been a time of rapid globalization in the development, manufacture, marketing, and distribution of medical products and technologies. Increasingly, research on the safety and effectiveness of new drugs is being conducted in countries with little experience in regulation of medical product development. Demand has been increasing for globally harmonized, science-based standards for the development and evaluation of the safety, quality, and efficacy of medical products. Consistency of such standards could improve the efficiency and clarity of the drug development and evaluation process and, ultimately, promote and enhance product quality and the public health. To explore the need and prospects for greater international regulatory harmonization for drug development, the IOM Forum on Drug Discovery, Development, and Translation hosted a workshop on February 13-14, 2013. Discussions at the workshop helped identify principles, potential approaches, and strategies to advance the development or evolution of more harmonized regulatory standards. This document summarizes the workshop.
Keywords: Health and Medicine

Critical Aspects of EPA's IRIS Assessment of Inorganic Arsenic: Interim Report - National Research Council (The National Academies Press, 2013)
The US Environmental Protection Agency (EPA) Integrated Risk Information System (IRIS) program develops toxicologic assessments of environmental contaminants. IRIS assessments provide hazard identification and dose-response assessment information. The information is then used in conjunction with exposure information to characterize risks to public health and may be used in risk-based decisionmaking, in regulatory actions, and for other risk-management purposes. Since the middle 1990s, EPA has been in the process of updating the IRIS assessment of inorganic arsenic. In response to a congressional mandate for an independent review of the IRIS assessment of inorganic arsenic, EPA requested that the National Research Council convene a committee to conduct a two-phase study. Critical Aspects of EPA's IRIS Assessment of Inorganic Arsenic is the report of the first phase of that study. This report evaluates critical scientific issues in assessing cancer and noncancer effects of oral exposure to inorganic arsenic and offers recommendations on how the issues could be addressed in EPA's IRIS assessment.
Keywords: Environment and Environmental Studies

Measuring What We Spend: Toward a New Consumer Expenditure Survey - National Research Council (The National Academies Press, 2013)
The Consumer Expenditure (CE) surveys are the only source of information on the complete range of consumers' expenditures and incomes in the United States, as well as the characteristics of those consumers. The CE consists of two separate surveys: (1) a national sample of households interviewed five times at three-month intervals; and (2) a separate national sample of households that complete two consecutive one-week expenditure diaries. For more than 40 years, these surveys, the responsibility of the Bureau of Labor Statistics (BLS), have been the principal source of knowledge about changing patterns of consumer spending in the U.S. population. In February 2009, BLS initiated the Gemini Project, the aim of which is to redesign the CE surveys to improve data quality through a verifiable reduction in measurement error with a particular focus on underreporting. The Gemini Project initiated a series of information-gathering meetings, conference sessions, forums, and workshops to identify appropriate strategies for improving CE data quality. As part of this effort, BLS requested the National Research Council's Committee on National Statistics (CNSTAT) to convene an expert panel to build on the Gemini Project by conducting further investigations and proposing redesign options for the CE surveys. The charge to the Panel on Redesigning the BLS Consumer Expenditure Surveys includes reviewing the output of a Gemini-convened data user needs forum and methods workshop and convening its own household survey producers workshop to obtain further input. In addition, the panel was tasked to commission options from contractors for consideration in recommending possible redesigns. The panel was further asked by BLS to create potential redesigns that would put a greater emphasis on proactive data collection to improve the measurement of consumer expenditures. Measuring What We Spend summarizes the deliberations and activities of the panel, discusses the conclusions about the uses of the CE surveys and why a redesign is needed, as well as recommendations for the future.
Keywords: Industry and Labor; Behavioral and Social Sciences; Surveys and Statistics

Environmental Decisions in the Face of Uncertainty - Institute of Medicine (The National Academies Press, 2013)
The U.S. Environmental Protection Agency (EPA) is one of several federal agencies responsible for protecting Americans against significant risks to human health and the environment. As part of that mission, EPA estimates the nature, magnitude, and likelihood of risks to human health and the environment; identifies the potential regulatory actions that will mitigate those risks and protect public health1 and the environment; and uses that information to decide on appropriate regulatory action. Uncertainties, both qualitative and quantitative, in the data and analyses on which these decisions are based enter into the process at each step. As a result, the informed identification and use of the uncertainties inherent in the process is an essential feature of environmental decision making. EPA requested that the Institute of Medicine (IOM) convene a committee to provide guidance to its decision makers and their partners in states and localities on approaches to managing risk in different contexts when uncertainty is present. It also sought guidance on how information on uncertainty should be presented to help risk managers make sound decisions and to increase transparency in its communications with the public about those decisions. Given that its charge is not limited to human health risk assessment and includes broad questions about managing risks and decision making, in this report the committee examines the analysis of uncertainty in those other areas in addition to human health risks. Environmental Decisions in the Face of Uncertainty explains the statement of task and summarizes the findings of the committee.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Directed Evolution for Development and Production of Bioactive Agents: A Meeting Summary - National Research Council (The National Academies Press, 2013)
In 2012, the Defense Intelligence Agency (DIA) approached the National Research Council and asked that a committee be formed to develop a list of workshop topics to explore the impact of emerging science and technology. One topic that came out of that list was directed evolution for development and production of bioactive agents. This workshop was held on February 21-22, 2013. Directed Evolution for Development and Production of Bioactive Agents explains the objectives of the workshop, which were to explore the potential use of directed evolution1 for military science and technology. Understanding the current research in this area, and the potential opportunities for U.S. adversaries to use this research, might allow the DIA to advise U.S. policy makers in an appropriate and timely manner. The workshop featured invited presentations and discussions that aimed to: -Inform the U.S. intelligence community of the current status of directed evolution technology and related research, and -Discuss possible approaches involving directed evolution that might be used by an adversary to develop toxic biological agents that could pose a threat to the United States or its allies, and how they could be identified. Members of the Committee on Science and Technology for Defense Warning planned the agenda for the workshop, selected the presenters, and helped moderate discussions in which meeting participants probed issues of national security related to directed evolution in an effort to gain an understanding of potential vulnerabilities. Experts were invited from the areas of directed evolution, biosynthesis, detection, and biological agents.
Keywords: Conflict and Security Issues

Harnessing Operational Systems Engineering to Support Peacebuilding: Report of a Workshop by the National Academy of Engineering and United States Institute of Peace Roundtable on Technology, Science, and Peacebuilding - National Academy of Engineering (The National Academies Press, 2013)
Operational systems engineering is a methodology that identifies the important components of a complex system, analyzes the relationships among those components, and creates models of the system to explore its behavior and possible ways of changing that behavior. In this way it offers quantitative and qualitative techniques to support the design, analysis, and governance of systems of diverse scale and complexity for the delivery of products or services. Many peacebuilding interventions function essentially as the provision of services in response to demands elicited from societies in crisis. At its core, operational systems engineering attempts to understand and manage the supply of services and product in response to such demands. Harnessing Operational Systems Engineering to Support Peacebuilding is the summary of a workshop convened in November 2012 by the Roundtable on Science, Technology, and Peacebuilding of the National Academy of Engineering and the United States Institute of Peace to explore the question "When can operational systems engineering, appropriately applied, be a useful tool for improving the elicitation of need, the design, the implementation, and the effectiveness of peacebuilding interventions?" The workshop convened experts in conflict prevention, conflict management, postconflict stabilization, and reconstruction along with experts in various fields of operational systems engineering to identify what additional types of nonnumerical systems methods might be available for application to peacebuilding.
Keywords: Engineering and Technology

Subjective Well-Being: Measuring Happiness, Suffering, and Other Dimensions of Experience - National Research Council (The National Academies Press, 2013)
Subjective well-being refers to how people experience and evaluate their lives and specific domains and activities in their lives. This information has already proven valuable to researchers, who have produced insights about the emotional states and experiences of people belonging to different groups, engaged in different activities, at different points in the life course, and involved in different family and community structures. Research has also revealed relationships between people's self-reported, subjectively assessed states and their behavior and decisions. Research on subjective well-being has been ongoing for decades, providing new information about the human condition. During the past decade, interest in the topic among policy makers, national statistical offices, academic researchers, the media, and the public has increased markedly because of its potential for shedding light on the economic, social, and health conditions of populations and for informing policy decisions across these domains. Subjective Well-Being: Measuring Happiness, Suffering, and Other Dimensions of Experience explores the use of this measure in population surveys. This report reviews the current state of research and evaluates methods for the measurement. In this report, a range of potential experienced well-being data applications are cited, from cost-benefit studies of health care delivery to commuting and transportation planning, environmental valuation, and outdoor recreation resource monitoring, and even to assessment of end-of-life treatment options. Subjective Well-Being finds that, whether used to assess the consequence of people's situations and policies that might affect them or to explore determinants of outcomes, contextual and covariate data are needed alongside the subjective well-being measures. This report offers guidance about adopting subjective well-being measures in official government surveys to inform social and economic policies and considers whether research has advanced to a point which warrants the federal government collecting data that allow aspects of the population's subjective well-being to be tracked and associated with changing conditions.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Reducing Tobacco-Related Cancer Incidence and Mortality: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Tobacco use is the leading cause of preventable death in United States, causing more than 440,000 deaths annually and resulting in $193 billion in health-related economic losses each year—$96 billion in direct medical costs and $97 billion in lost productivity. Since the first U.S. Surgeon General's report on smoking in 1964, more than 29 Surgeon General's reports, drawing on data from thousands of studies, have documented the overwhelming and conclusive biologic, epidemiologic, behavioral, and pharmacologic evidence that tobacco use is deadly. This evidence base links tobacco use to the development of multiple types of cancer and other life-threatening conditions, including cardiovascular and respiratory diseases. Smoking accounts for at least 30 percent of all cancer deaths, and 80 percent of lung cancer deaths. Despite the widespread agreement on the dangers of tobacco use and considerable success in reducing tobacco use prevalence from over 40 percent at the time of the 1964 Surgeon General's report to less than 20 percent today, recent progress in reducing tobacco use has slowed. An estimated 18.9 percent of U.S. adults smoke cigarettes, nearly one in four high school seniors smoke, and 13 percent of high school males use smokeless tobacco products. In recognition that progress in combating cancer will not be fully achieved without addressing the tobacco problem, the National Cancer Policy Forum of the Institute of Medicine (IOM) convened a public workshop, Reducing Tobacco-Related Cancer Incidence and Mortality, June 11-12, 2012 in Washington, DC. In opening remarks to the workshop participants, planning committee chair Roy Herbst, professor of medicine and of pharmacology and chief of medical oncology at Yale Cancer Center and Smilow Cancer Hospital, described the goals of the workshop, which were to examine the current obstacles to tobacco control and to discuss potential policy, outreach, and treatment strategies that could overcome these obstacles and reduce tobacco-related cancer incidence and mortality. Experts explored a number of topics, including: the changing demographics of tobacco users and the changing patterns of tobacco product use; the influence of tobacco use on cancer incidence and cancer treatment outcomes; tobacco dependence and cessation programs; federal and state level laws and regulations to curtail tobacco use; tobacco control education, messaging, and advocacy; financial and legal challenges to tobacco control efforts; and research and infrastructure needs to support tobacco control strategies, reduce tobacco related cancer incidence, and improve cancer patient outcomes. Reducing Tobacco-Related Cancer Incidence and Mortality summarizes the workshop.
Keywords: Health and Medicine

Core Measurement Needs for Better Care, Better Health, and Lower Costs: Counting What Counts: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Health care quality and its affordability have become very pressing issues in the United States. All sectors of the country are attempting to push forward initiatives that will improve the health care system as well as the health of the American population in general. Despite the economical dedication to health care, about 1/5, the system remains uneven and fragmented, patient harm is quite common, care is often uncoordinated, and many more mishaps occur. There exists many obstacles to improve the nation's health care system; these include the capacity to reliably and consistently measure progress. In 2006 the Institute of Medicine (IOM) established the Roundtable on Value & Science-Driven Health Care which has since accelerated the development of a learning health system- one in which science, informatics, incentives, and culture are aligned to create a continuous learning loop. This learning loop would thus help make the health care system better. In response, the IOM organized a 2-day workshop to explore in depth the core measurement needs for population health, health care quality, and health care costs. The workshop hoped to gain a full understanding of how to improve the nation's measurement capacity to track progress in the health care system. Having this knowledge would help the nation get one step closer to the creation of an efficient learning loop. The workshop was divided into a series of sessions that focused on different aspects of measurement. Core Measurement Needs for Better Care, Better Health, and Lower Costs: Counting What Counts: Workshop Summary includes explanations and key details for these sessions: Vision, Current Measurement Capabilities, Specifying the Shape of a Core Metric Set, and Implementation. The report also features common themes within these areas, the workshop agenda, and information about those involved.
Keywords: Health and Medicine

Priorities for Research to Reduce the Threat of Firearm-Related Violence - Institute of Medicine; National Research Council (The National Academies Press, 2013)
In 2010, more than 105,000 people were injured or killed in the United States as the result of a firearm-related incident. Recent, highly publicized, tragic mass shootings in Newtown, CT; Aurora, CO; Oak Creek, WI; and Tucson, AZ, have sharpened the American public's interest in protecting our children and communities from the harmful effects of firearm violence. While many Americans legally use firearms for a variety of activities, fatal and nonfatal firearm violence poses a serious threat to public safety and welfare. In January 2013, President Barack Obama issued 23 executive orders directing federal agencies to improve knowledge of the causes of firearm violence, what might help prevent it, and how to minimize its burden on public health. One of these orders directed the Centers for Disease Control and Prevention (CDC) to, along with other federal agencies, immediately begin identifying the most pressing problems in firearm violence research. The CDC and the CDC Foundation asked the IOM, in collaboration with the National Research Council, to convene a committee tasked with developing a potential research agenda that focuses on the causes of, possible interventions to, and strategies to minimize the burden of firearm-related violence. Priorities for Research to Reduce the Threat of Firearm-Related Violence focuses on the characteristics of firearm violence, risk and protective factors, interventions and strategies, the impact of gun safety technology, and the influence of video games and other media.
Keywords: Behavioral and Social Sciences; Health and Medicine

Principles and Practices for a Federal Statistical Agency: Fifth Edition - National Research Council (The National Academies Press, 2013)
Publicly available statistics from government agencies that are credible, relevant, accurate, and timely are essential for policy makers, individuals, households, businesses, academic institutions, and other organizations to make informed decisions. Even more, the effective operation of a democratic system of government depends on the unhindered flow of statistical information to its citizens. In the United States, federal statistical agencies in cabinet departments and independent agencies are the governmental units whose principal function is to compile, analyze, and disseminate information for such statistical purposes as describing population characteristics and trends, planning and monitoring programs, and conducting research and evaluation. The work of these agencies is coordinated by the U.S. Office of Management and Budget. Statistical agencies may acquire information not only from surveys or censuses of people and organizations, but also from such sources as government administrative records, private-sector datasets, and Internet sources that are judged of suitable quality and relevance for statistical use. They may conduct analyses, but they do not advocate policies or take partisan positions. Statistical purposes for which they provide information relate to descriptions of groups and exclude any interest in or identification of an individual person, institution, or economic unit. Four principles are fundamental for a federal statistical agency: relevance to policy issues, credibility among data users, trust among data providers, and independence from political and other undue external influence. Principles and Practices for a Federal Statistical Agency: Fifth Edition explains these four principles in detail.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

The Informed Brain in a Digital World: Interdisciplinary Research Team Summaries (The National Academies Press, 2013)
Digital media provide humans with more access to information than ever before—a computer, tablet, or smartphone can all be used to access data online and users frequently have more than one device. However, as humans continue to venture into the digital frontier, it remains to be known whether access to seemingly unlimited information is actually helping us learn and solve complex problems, or ultimately creating more difficulty and confusion for individuals and societies by offering content overload that is not always meaningful. Throughout history, technology has changed the way humans interact with the world. Improvements in tools, language, industrial machines, and now digital information technology have shaped our minds and societies. There has always been access to more information than humans can handle, but the difference now lies in the ubiquity of the Internet and digital technology, and the incredible speed with which anyone with a computer can access and participate in seemingly infinite information exchange. Humans now live in a world where mobile digital technology is everywhere, from the classroom and the doctor's office to public transportation and even the dinner table. This paradigm shift in technology comes with tremendous benefits and risks. Interdisciplinary Research (IDR) Teams at the 2012 National Academies Keck Futures Initiative Conference on The Informed Brain in the Digital World explored common rewards and dangers to Humans among various fields that are being greatly impacted by the Internet and the rapid evolution of digital technology. Keynote speaker Clifford Nass of Stanford University opened the dialogue by offering insight into what we already know about how the "information overload" of the digital world may be affecting our brains. Nass presented the idea of the "media budget," which states that when a new media emerges, it takes time away from other media in a daily time budget. When additional media appear and there is no time left in a person's daily media budget, people begin to "double book" media time. Personal computers, tablets, and smartphones make it easy to use several media simultaneously, and according to Nass, this double-booking of media can result in chronic multitasking, which effects how people store and manage memory. Although current fast-paced work and learning environments often encourage multitasking, research shows that such multitasking is inefficient, decreases productivity, and may hinder cognitive function. National Academies Keck Future Initiative: The Informed Brain in a Digital World summarizes the happenings of this conference.
Keywords: Biology and Life Sciences; Engineering and Technology

Building the Illinois Innovation Economy: Summary of a Symposium - National Research Council (The National Academies Press, 2013)
Responding to the challenges of fostering regional growth and employment in an increasingly competitive global economy, many U.S. states and regions have developed programs to attract and grow companies as well as attract the talent and resources necessary to develop innovation clusters. These state and regionally based initiatives have a broad range of goals and increasingly include significant resources, often with a sector focus and often in partnership with foundations and universities. These are being joined by recent initiatives to coordinate and concentrate investments from a variety of federal agencies that provide significant resources to develop regional centers of innovation, business incubators, and other strategies to encourage entrepreneurship and high-tech development. Building the Illinois Innovation Economy is a study of selected state and regional programs to identify best practices with regard to their goals, structures, instruments, modes of operation, synergies across private and public programs, funding mechanisms and levels, and evaluation efforts. This report reviews selected state and regional efforts to capitalize on federal and state investments in areas of critical national needs. This review includes both efforts to strengthen existing industries as well as specific new technology focus areas such as nanotechnology, stem cells, and energy in order to improve our understanding of program goals, challenges, and accomplishments. As a part of this review, The Committee on Competing in the 21st Century: Best Practice in State and Regional Innovation Initiatives is convening a series of public workshops and symposia involving responsible local, state, and federal officials and other stakeholders. These meetings and symposia will enable an exchange of views, information, experience, and analysis to identify best practice in the range of programs and incentives adopted. Building the Illinois Innovation Economy summarizes discussions at these symposia, fact-finding meetings, and commissioned analyses of existing state and regional programs and technology focus areas, the committee will subsequently produce a final report with findings and recommendations focused on lessons, issues, and opportunities for complementary U.S. policies created by these state and regional initiatives.
Keywords: Industry and Labor